2020
DOI: 10.1002/slct.202000497
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Performance of In/HZSM‐5 for Coupling Propane with CO2 to Propylene

Abstract: The dehydrogenation of propane to propylene is endothermic reaction will generate hydrogen, while the hydrogenation of CO2 to light olefins is exothermic reaction with hydrogen as reactant. Using the CO2 hydrogenation reaction to consume the hydrogen from the propane dehydrogenation reaction, which is more beneficial to propylene generation. Thus, a promising approach of coupling propane with CO2 to produce propylene was proposed. A simple wetness impregnation method was used to prepare the In/HZSM‐5 composite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 73 publications
0
17
0
Order By: Relevance
“… 62 There were two characteristic peaks of In at 440.7–448 and 448–455.2 eV, both being ascribed to In 2 O 3 . 63 The fitting peaks of the Ni 2p region were NiO (857.1–860.8 eV for Ni 2p 3/2 and 875.0–878.5 eV for Ni 2p 1/2 ) and satellite peaks (862.2–864.0 eV for Ni 2p 3/2 and 880.8–882.5 eV for Ni 2p 1/2 ). 64 Molybdenum species have many chemical states in zeolite after hydrogen reduction, but only MoO 3 is present by oxidation treatment, and the peaks emerging at 232.9 and 235.9 eV were attributed to MoO 3 .…”
Section: Results and Discussionmentioning
confidence: 94%
“… 62 There were two characteristic peaks of In at 440.7–448 and 448–455.2 eV, both being ascribed to In 2 O 3 . 63 The fitting peaks of the Ni 2p region were NiO (857.1–860.8 eV for Ni 2p 3/2 and 875.0–878.5 eV for Ni 2p 1/2 ) and satellite peaks (862.2–864.0 eV for Ni 2p 3/2 and 880.8–882.5 eV for Ni 2p 1/2 ). 64 Molybdenum species have many chemical states in zeolite after hydrogen reduction, but only MoO 3 is present by oxidation treatment, and the peaks emerging at 232.9 and 235.9 eV were attributed to MoO 3 .…”
Section: Results and Discussionmentioning
confidence: 94%
“…In addition, the Mix C catalyst revealed the highest HC selectivity with no detectable DME in the product stream. [30] Nevertheless, the major product in the HC distribution was C 5 + , reflecting that almost all the MeOH was converted to DME and then the DME was completely converted to HCs at the zeolite stage, but the separation of the CZZA and HY zeolite catalyst stages increased the retention time of intermediate products that could be continuously converted to higher HC products. Therefore, the Mix A catalyst exhibited the best catalytic performance.…”
Section: Effect Of the Mixing Methodsmentioning
confidence: 98%
“…Therefore, the addition of zeolite contributes to suppress the RWGS reaction as follows: The MeOH and DME formed from the CO 2 hydrogenation reaction on CZZA are dehydrated into HCs and H 2 O on the HY zeolite, and the H 2 O formed promoted the concentration of vapor around the CZZA metal catalyst nearby, and so the RWGS reaction was subsequently suppressed. In addition, the Mix C catalyst revealed the highest HC selectivity with no detectable DME in the product stream [30] . Nevertheless, the major product in the HC distribution was C 5+ , reflecting that almost all the MeOH was converted to DME and then the DME was completely converted to HCs at the zeolite stage, but the separation of the CZZA and HY zeolite catalyst stages increased the retention time of intermediate products that could be continuously converted to higher HC products.…”
Section: Reaction Conditionsmentioning
confidence: 97%
“…They proposed that the metallic In 0 species was crucial for the dehydrogenation, and basic sites of Al 2 O 3 were responsible for the activation of CO 2 to promote the RWGS reaction [133,134]. In addition, Ma et al found that there was no induction period over In/ HZSM-5 catalyst in the CO 2 -ODHP reaction, at the same time, the formation of In 0 would lead to a decrease in activity of In/HZSM-5 [135]. Thus, they considered that In 3?…”
Section: Indium-based Catalystsmentioning
confidence: 99%